Complementary Therapy for Treating Pruritus in Chronic Kidney Disease Patients: Systematic Literature Review - Mita Majdina Anugrah; Nisrina Nur Aini; Nunung Siti Sukaesih; Dedah Ningrum; Helmalia Putri Arabani; Rina Firdayanti Nurhadi; Zahra Marsyifa Rohman; Aditya Muhamad Fadilah (Sarana Ilmu Indonesia (salnesia), 2026)
Uremic pruritus was a distressing symptom frequently experienced by patients undergoing hemodialysis, characterized by widespread daily itching that was symmetrical, bilateral, without dermatomal patterns or primary skin lesions. The symptoms could be generalized or localized, particularly on the back, abdomen, and arms. This systematic review aimed to identify complementary therapy methods and their frequency of administration in managing pruritus among patients with Chronic Kidney Disease-associated Pruritus (CKD-aP) undergoing hemodialysis. The study used a systematic literature review design with a PICOST approach. The included studies were randomized controlled trials and quasi-experimental studies published between 2014 and 2024. The literature search was conducted through PubMed, Springer Link, ScienceDirect, SAGE Journals, Taylor & Francis, and Semantic Scholar. Article selection included duplicate removal using Mendeley, followed by title, abstract, and full-text screening based on inclusion and exclusion criteria. A total of 13 articles met the eligibility criteria. The results showed that acupressure, acupuncture, foot reflexology massage, clove oil, violet oil, virgin coconut oil, peppermint oil, EPA supplementation, and dill oil were effective in reducing pruritus among CKD-aP patients. The most frequently used interventions were peppermint oil and virgin coconut oil through topical application or massage. Complementary therapies had the potential to serve as effective adjunctive treatments, although their effectiveness varied and some studies had methodological limitations.